1999
DOI: 10.1002/(sici)1097-4695(199907)40:1<45::aid-neu4>3.3.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

Aggregates of acetylcholine receptors are not observed under anti‐agrin staining Schwann cell processes at the frog neuromuscular junction

Abstract: The frog neuromuscular junction offers a unique structure in which to observe fine details in the relationship between the motor neuron, muscle, and Schwann cell, which together comprise the neuromuscular junction. Schwann cell processes that extended from the synapse stained positively with anti-agrin antibodies. Immunocytochemistry revealed strong anti-agrin staining of the extracellular matrix surrounding the entire Schwann cell and the Schwann cell processes come in close contact with the muscle fiber. Dua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2001
2001
2008
2008

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…Although the predominant cell type in the sciatic nerve is the Schwann cell, the epineurial sheath, which is rich in fibroblasts, was routinely removed to ensure that we used primarily Schwann cells for the RT-PCR study. We found that frog Schwann cells along the sciatic nerve expressed not only the inactive isoform B0, as shown previously (Werle et al, 1999), but also the active isoforms B11 and B19 ( Fig. 1 A, lane 6 ).…”
Section: Expression Of Agrin Isoforms In Developing and Adult Schwannsupporting
confidence: 88%
See 3 more Smart Citations
“…Although the predominant cell type in the sciatic nerve is the Schwann cell, the epineurial sheath, which is rich in fibroblasts, was routinely removed to ensure that we used primarily Schwann cells for the RT-PCR study. We found that frog Schwann cells along the sciatic nerve expressed not only the inactive isoform B0, as shown previously (Werle et al, 1999), but also the active isoforms B11 and B19 ( Fig. 1 A, lane 6 ).…”
Section: Expression Of Agrin Isoforms In Developing and Adult Schwannsupporting
confidence: 88%
“…To confirm the identity of agrin transcripts in Schwann cells, each PCR fragment was subcloned and sequenced. PCR with nested primers (see Materials and Methods) were also used to further confirm that these PCR products were frog agrin gene fragments (Werle et al, 1999). Our results showed that agrin expression in adult Schwann cells was similar to that in the spinal cord neurons, except for the absence of the B8 isoform.…”
Section: Expression Of Agrin Isoforms In Developing and Adult Schwannmentioning
confidence: 52%
See 2 more Smart Citations
“…Gels were visualized using a UV transilluminator, and images were taken using a digital camera. For agrin, primers flanking the frog agrin alternative splicing site B were designed based on the GenBank sequence AF096690 (Werle et al, 1999): forward, 5Ј-TCT CTG GAG GAC AAT GTG AGA AAG C-3Ј; and reverse, 5Ј-CCT GAG TGG CTT CAG TCT TTA TGC-3Ј. The housekeeping gene glyceraldehyde 3-phosphate dehydrogenase (GAPDH ) was used to confirm the equal loading of samples for the reverse transcription and PCRs.…”
Section: Methodsmentioning
confidence: 99%